Effect of Pause Size and its Number on Egg Mass for a Stock of White Leghorn in Iraq - Al-Nedawi, A.M.; Al-Samarai, F.R.; Al-Soudi, K.A. (International Journal of Poultry Science, 2008)
This study included 336 Leghorn hens and was conducted at poultry farm, Department of Animal Resources /Agriculture College / University of Baghdad / Iraq, from 15/6/2005 to 30/9/2005. The aim of the present study was to investigate the effects of pause size and pause number on egg mass in White Leghorn during the first 100 day before onset of laying the first egg. General Linear Model (GLM) within SAS program was used to study the effect of some fixed effects which included (hatch and age at sexual maturity ) on pause size and pause number beside studying the effect of hatch, weight at sexual maturity, pause size and pause number on egg mass. The overall means for pause size, pause number, egg mass were 2.27 days, 15.48 pauses and 3495.02 gm respectively. The effect of hatch was significant (P < 0.05) on pause size and pause number, whereas the effect of weight at sexual maturity on the same traits was not. Egg mass was affected significantly (P < 0.01) by pause size and pause number, but the effect of hatch and weight at sexual maturity was not significant.